Fall in immune complex levels during gold treatment of rheumatoid arthritis. Issue 6 (December 1981) - Highton, J; Panayi, G S; Shepherd, P; Faith, A; Griffin, J; Gibson, T
Abstract : Prior to starting gold treatment 30 patients with rheumatoid arthritis had an elevated mean level of circulating immune complexes measured by Clq binding activity. Gold treatment led to an improvement in disease reflected by significant falls in erythrocyte sedimentation rate (p less than 0.001), C-reactive protein (p less than 0.01), Ritchie articular index (p less than 0.001), and duration of morning stiffness (p less than 0.05). Concurrently immune complex levels fell, and this change first reached significance after 3 months' treatment (p less than 0.05). Serum Clq binding activity was not related to clinical and laboratory measurements of joint inflammation. This suggested to us that there is no direct immunopathological relationship between circulating immune complexes and joint inflammation in rheumatoid arthritis. Serum Clq binding activity was strongly related to IgM-RF levels measured at latex titre (r - 0.7, p less than 0.001). Removal of immune complexes from serum with Sepharose 4B-staph A (staphylococcal protein A) led to a fall in IgM-RF from 2 mg/ml (2 g/l) to 0.4 mg/ml (0.4 g/l). This suggests that the reason for the relationship between Clq BA and IgM-RF is that, on average 80% of serum IgM-RF exists as part of immune complexes containing IgG.